International Competitiveness Impacts of FDI in CEECs - Gabor Hunya (The Vienna Institute for International Economic Studies (wiiw), 2000)
This paper follows the definition of international competitiveness of countries (nations) as defined by Trabold (1995) including the ability to sell, the ability to attract FDI and the ability to adjust - all these leading to the ability to earn. These components can be measured by specific economic indicators and brought into relationship with FDI and the performance of foreign affiliates in a country. The analysis focuses on five transition countries Estonia, the Czech Republic, Hungary, Poland and Slovenia (CEEC?5). These are the most advanced among the transition countries in terms of per capita GDP, FDI penetration and economic transformation. This paper contributes to the discussion on competitiveness by going through a number of industry competitiveness indicators attracting FDI, foreign penetration of industries, productivity levels and development, market shares in the EU. In order to measure the influence of FDI on the competitiveness in manufacturing, a unique database was set up based on company balance sheets in the five countries. The economic performance of the foreign affiliates could be compared with that of domestic enterprises. The highest share of FIEs (foreign investment enterprises) by all indicators was reached by Hungary in each year between 1993 and 1998. 70% of manufacturing sales came from FIEs, which employed 45% of the manufacturing labour force in 1998. The second place is occupied by Poland with 41% of sales and 26% of employment. The Czech Republic ranks third, with 32% and 20% respectively. The difference between Hungary on the one hand and the Czech Republic and Poland on the other was three times in 1994 and narrowed to two times in 1998. The most dynamic increase was recorded in the Czech Republic. In Slovenia and Estonia, foreign penetration is lower and increased more slowly than in the other countries. The positive link between foreign penetration and various components of international competitiveness holds true both at the aggregate and the sectoral levels. It is obvious that the activity of a strong foreign sector in manufacturing increases international competitiveness. In 1994-1998 GDP growth, productivity growth, structural change and profit rates were higher in countries with a stronger presence of FDI. The deeper the foreign penetration, the faster was the speed of structural change Hungary was first, followed by the Czech Republic and Poland in the period 1996?1998. This is relevant both for the change in the output structure and the country's exports to the EU. The size and industry distribution of foreign penetration depends on industry-specific features and on the characteristics of the privatization policy. The foreign presence remained relatively small in branches with great structural difficulties and oversized capacities, such as the steel industry. Privatization is not enough to set restructuring of these industries in motion. Sectoral policy and financial restructuring is necessary to make companies attractive for foreign take?overs. A duality between foreign- and domestic-dominated industries appeared in all countries and has been growing over time. It can be observed between modern, foreign-dominated industries on the one hand and traditional industries with both domestic and foreign companies on the other. It is also present as a foreign-domestic gap within the industries with both foreign and domestic companies. The dichotomy of productivity and profit rates between the foreign- and the domestic-owned companies in one and the same industry is largest in Hungary and smallest in Slovenia. In Slovenia the balanced relationship between the domestic and the foreign sector is coupled with a low average rate of foreign penetration and a relatively low presence of technology-intensive industries. The small gap between the foreign and the domestic sector may indicate a slow rate of technological progress and not spill?overs.
Keywords: D20; L50; L60; F20; F40; 330; foreign direct investment; competitiveness; CEECs; manufacturing; economic policy